2011
DOI: 10.1111/j.1476-5381.2011.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids and traumatic brain injury

Abstract: Traumatic brain injury (TBI) represents the leading cause of death in young individuals. It triggers the accumulation of harmful mediators, leading to secondary damage, yet protective mechanisms are also set in motion. The endocannabinoid (eCB) system consists of ligands, such as anandamide and 2-arachidonoyl-glycerol (2-AG), receptors (e.g. CB1, CB2), transporters and enzymes, which are responsible for the 'on-demand' synthesis and degradation of these lipid mediators. There is a large body of evidence showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 90 publications
6
94
0
2
Order By: Relevance
“…38 The anti-inflammatory and neuroprotective behaviors of 2-AG suggest that manipulation of 2-AG signaling may provide novel therapeutic interventions to prevent TBIinduced neuropathologic events. 22 MAGL is the primary enzyme degrading 2-AG in the brain. 14,15 Previous studies demonstrated that MAGL inactivation suppresses inflammatory cytokines in response to proinflammatory insults and neurodegeneration in an MPTP model of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The anti-inflammatory and neuroprotective behaviors of 2-AG suggest that manipulation of 2-AG signaling may provide novel therapeutic interventions to prevent TBIinduced neuropathologic events. 22 MAGL is the primary enzyme degrading 2-AG in the brain. 14,15 Previous studies demonstrated that MAGL inactivation suppresses inflammatory cytokines in response to proinflammatory insults and neurodegeneration in an MPTP model of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,27 In addition, inhibition of CB1 receptors only partly blocks 2-AG-produced neuroprotective effects in TBI. 22 This suggests that there may be other mechanisms mediating the anti-neuroinflammatory and neuroprotective effects produced by inhibition of 2-AG metabolism. 38 It has been proposed that these beneficial effects may result from the reduction in metabolites of 2-AG when MAGL is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-AG released into the synaptic cleft seems to be rapidly inactivated by uptake into neurons (23). This 2-AGinduced retrograde signaling process seems to be involved in widespread effects, including synaptic plasticity (24), analgesia (25), neuroprotection and neurotoxicity (26,27), food intake (24,28), and also in the baroreflexevoked central sympathetic modulation (29). Recently, we reported that central pretreatment with AM 251 (an antagonist of cannabinoid CB 1 receptors) or AM 404 (an uptake-inhibitor of endocannabinoid) potentiated or reduced the centrally administered bombesin-induced elevation of plasma catecholamines, respectively (16).…”
Section: Stimulatory and Inhibitory Roles Of Brain 2-arachidonoylglycmentioning
confidence: 99%
“…Although there is currently no unequivocal biological explanation for this observation, there is clear evidence that ECs are markedly increased in response to pathogenic events in the brain (Shohami et al, 2011). Numerous experimental studies on models of brain toxicity, neuroinflammation, and trauma support the notion that ECs are part of the brain ' s compensatory or repair mechanisms (Shohami et al, 2011 possible neuroprotective effect of 2-AG (Kreutz et al, 2009;Lourbopoulos et al, 2011). Patients with an inadequately low perioperative 2-AG response might be at risk for early postoperative ACD/delirium and for the later development of depression.…”
Section: Discussionmentioning
confidence: 99%